Sclerosing mesenteritis mimicking metachronous peritoneal metastases from descending colon adenocarcinoma - Toshifumi Watanabe (World Journal of Surgical Oncology, 2017)
Abstract Background Sclerosing mesenteritis is a non-neoplastic inflammatory disease that occurs in the bowel mesentery. Distinguishing sclerosing mesenteritis from neoplasms may be difficult because of the clinical and radiographic similarities between the two disease entities. Case presentation We report a case of sclerosing mesenteritis mimicking peritoneal metastases of colorectal carcinoma. A 73-year-old man with stage II descending colon adenocarcinoma with poor prognostic features was found to have developed left lower abdominal quadrant masses on computed tomography (CT) 9 months after undergoing radical surgery. These masses were diagnosed as peritoneal metastases because they grew in size and displayed fluorodeoxyglucose (FDG) uptake 3 months later; thus, a laparotomy was performed. The masses, which were localized in the jejunal mesentery, were excised completely via segmental jejunal resection. Histopathological analysis confirmed that the masses were sclerosing mesenteritis. The patient showed no signs of sclerosing mesenteritis or colorectal carcinoma recurrence during follow-up. Conclusions In patients suspected of having localized peritoneal metastasis from malignancies, any masses must be sampled by surgical excisional biopsy and subsequently examined to rule out alternative diagnoses, such as sclerosing mesenteritis.